Informality and productivity in the labor market: Peru 1986-2001 - Alberto Chong; José Galdo; Jaime Saavedra (Inter-American Development Bank, Research Department, 2007)
Peru has one of the highest informality rates in Latin America, with almost 60 percent of the urban labor force working at the margins of labor market legislation or in microenterprises that lack basic labor market standards (Marcouiller, Ruiz de Castilla, and Woodruff, 1997). This paper identifies two factors that can explain the variation in informality rates in the 1990s. First, Peru experienced a steady increase in employment allocation in traditionally 'informal' sectors - in particular, retail trade and transport. Second, there was a sharp increase in nonwage labor costs, despite a reduction in the average productivity of the economy. In addition, the paper illustrates the negative correlation between productivity and informality by evaluating the impacts of the PROJOVEN youth training program.
Keywords: 330